Environmental Forensic Techniques in Identifying the Sources of 16 USEPA Priority Pollutants Polycyclic Aromatic Hydrocarbons (PAHs) at the Langat River, Selangor, Malaysia - Afiqah Mohamd Tahir, Nurul; Juahir, Hafizan; Pauzi Zakaria, Mohamad; Md Zain, Sharifuddin; Retnam, Ananthy; Sin Sing, Tan; Manan, Norazida; Ekhwan Toriman, Mohd; Ismail, Azimah; Khairul Amri Kamarudin, Mohd; Ghazali, Adiana; Abd. Wahab, Noorjima (International Journal of Engineering and Technology, 2018)
Twenty-two surface sediment samples were collected from the Langat River, Selangor, Malaysia in January 2010. The concentration of 16 USEPA priority PAHs were determined and quantified by gas chromatography coupled with mass spectrometry detector (GC-MS). The 16 PAHs concentration ranged from 37.91 to 299.68 ng/g dry weight and are within low to moderate pollution range. Cluster analysis showed that SL08, SL09, SL10, SL15 and SL22 can be discriminated as having high pollution loading PAHs due to industrialized region and shipping boat traffic. In this work, Principal Component Analysis (PCA) and PCA association with Multiple Linear Regressions (PCA-MLR) to identify and apportion possible sources of PAHs. Three sources of PAHs were identified: (1) traffic emission (91.57%); (2) coal or wood combustion (6.63%); and (3) spillage of petroleum based products (1.80%). Langat River is highly contaminated by PAHs from pyrogenic sources, in particular 4 rings PAHs (28.87-79.52%) and 5 to 6 rings PAHs (2.69-57.44%).
Keywords: Langat River; polycyclic aromatic hydrocarbons; cluster analysis; principal component analysis; multiple linear regressions